2010
DOI: 10.1371/journal.pone.0015317
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MicroRNA Expression in the Prepubertal Testis

Abstract: Only thirteen microRNAs are conserved between D. melanogaster and the mouse; however, conditional loss of miRNA function through mutation of Dicer causes defects in proliferation of premeiotic germ cells in both species. This highlights the potentially important, but uncharacterized, role of miRNAs during early spermatogenesis. The goal of this study was to characterize on postnatal day 7, 10, and 14 the content and editing of murine testicular miRNAs, which predominantly arise from spermatogonia and spermatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 53 publications
8
61
0
1
Order By: Relevance
“…S1B). These data are in agreement with several recent reports (17,(22)(23)(24) showing much higher levels of miR-449 in adult than in prepubertal mouse testes. Among miRNAs highly enriched in P60 compared with P7, miR-449 displayed the most drastic up-regulation with 67-and 253-fold increases by microarray and qPCR assays, respectively (supplemental Fig.…”
Section: Mir-449 Is Significantly Up-regulated With Progression Ofsupporting
confidence: 94%
“…S1B). These data are in agreement with several recent reports (17,(22)(23)(24) showing much higher levels of miR-449 in adult than in prepubertal mouse testes. Among miRNAs highly enriched in P60 compared with P7, miR-449 displayed the most drastic up-regulation with 67-and 253-fold increases by microarray and qPCR assays, respectively (supplemental Fig.…”
Section: Mir-449 Is Significantly Up-regulated With Progression Ofsupporting
confidence: 94%
“…Third, our DNA-FISH plus RNAPII colocalization studies showed that Type II and III X-linked miRNA (and autosomal control mRNA) gene loci at which we detected positive RNA-FISH signals were also occupied by RNAPII in pachytene spermatocytes, whereas Type I X-linked miRNA gene loci as well as X-linked mRNA gene loci which showed no RNA-FISH signals were not occupied by RNAPII. Taken together, and in combination with data previously reported by us (Song et al, 2009) and others (Marcon et al, 2008;Buchold et al, 2010;Modzelewski et al, 2012), there is now compelling evidence that Type II and III X-linked miRNA genes do indeed escape MSCI and continue to undergo active, de novo transcription throughout first meiotic prophase. As such, Type II and III X-linked miRNA genes stand as the only X-linked genes shown to date to escape the otherwise panchromosomal effects of MSCI.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, whereas numerous X-linked mRNA genes have been shown to escape X chromosome inactivation in female somatic cells, no X-linked mRNA gene has yet been shown unequivocally to escape MSCI in primary spermatocytes. Nevertheless, we (Song et al, 2009) and others (Marcon et al, 2008;Buchold et al, 2010;Modzelewski et al, 2012;Liu et al, 2015) have reported that several X-linked miRNAs show an increase in steady-state levels during first meiotic prophase, including in pachytene spermatocytes.…”
Section: Discussionmentioning
confidence: 61%
“…In the past several years, a number of miRNA expression profiles have been identified in the murine testes by miRNA microarrays, RT-PCR or small RNA sequencing technology (Hayashi et al 2008, Buchold et al 2010, Jung et al 2010. The expression profiling of interesting miRNAs in the testis has been outlined in Table 1, and their potential roles in regulating SSC selfrenewal and differentiation are illustrated in Fig.…”
Section: The Roles Of Mirnas In Ssc Self-renewal and Differentiationmentioning
confidence: 99%